Beckett's and Murakami's 'Vaguened' Worlds - Byrne Keane, Alicia Paula (Trinity College Dublin. School of English. Discipline of English, 2022)
On the first page of the first Happy Days typescript, Samuel Beckett wrote the self-instruction vaguen it : the obscuring and occasional erasure of contextual markers occurs frequently throughout his body of work. It is arguable that contemporary Japanese author Haruki Murakami writes in a similarly vague way, as culturally specific references in his oeuvre often appear denuded of their surrounding context. Crucially, both Beckett s and Murakami s writing is informed by self-translation. In a manner interestingly relevant to their translational positions, both authors frequently use domestic settings as a means by which to apparently shut out the outside world in their work, potentially further evading culturally specific depictions of setting. This thesis expands on such a comparative study in order to discuss the politics of vaguening on an international scale. If canon formation has so often occurred along Anglocentric and Eurocentric lines, it follows that many works judged vague may adhere to a biased form of universality. Vaguening may only be deemed comprehensible or acceptable when employed as a technique by authors whose experiences have been well represented in literary media. Throughout this thesis, I chart the presence of vague interior settings in a range of 20th century and contemporary texts, in order to discuss the role of vaguening in a time of hopefully increasing literary diversity. With the aid of close readings of several extracts from texts by Beckett and Murakami, I contrast the occasionally fetishised, translational border positions assumed by both authors with works from multilingual and decolonial contexts around the world. I conclude with a discussion of vaguening alongside constructs of world literature , ending with a consideration of triviality versus profundity in the reception of domestically focused texts from self-translating female authors. In this manner, I aim to elucidate the often overdetermined meanings of vagueness when applied to internationally disseminated literature, charting the role of this term in othering, decolonial reappropriations, and (mis)translational contexts.
APPROVED
Keywords: Murakami Studies; World Literature; Translation Studies; Irish Studies; Beckett Studies; Japanese Studies; Postcolonial Studies; Domestic Space; Gender Studies